2010
DOI: 10.1111/j.1524-4741.2009.00828.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Surgical Treatment for Women with Breast Cancer in Relation to Age

Abstract: Although treatment recommendations have been advocated for all women with early breast cancer regardless of age, it is generally accepted that different treatments are preferred based on the age of the patient. The aim of this study was to assess the pattern of breast cancer surgery after adjusting for other major prognostic factors in relation to patient age. Data on cancer characteristics and surgical procedures in 31,298 patients with early breast cancer reported to the National Breast Cancer Audit between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 26 publications
2
18
1
1
Order By: Relevance
“…Wang, on a survey of 31298 patients with early BC from Australia and New Zealand between 1999 and 2006, observed that women older than 70 years were more likely to receive mastectomy in the place of breast conserving surgery or no surgery at all (3.5%) than younger counterpart [83]. …”
Section: Resultsmentioning
confidence: 99%
“…Wang, on a survey of 31298 patients with early BC from Australia and New Zealand between 1999 and 2006, observed that women older than 70 years were more likely to receive mastectomy in the place of breast conserving surgery or no surgery at all (3.5%) than younger counterpart [83]. …”
Section: Resultsmentioning
confidence: 99%
“…The tendency towards more radical surgery in older women has been reported by others and was attributed to a belief that mastectomy is safer and to a desire to avoid radiation therapy [20,22] . The proportion of sentinel biopsies relative to axillary dissections was similar in both age groups; however, a larger percentage of older patients did not undergo any axillary surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, patients in the older group may not have been referred for breast cancer screening at all given the recommended age limit for screening of 70-75 years. The comparable nodal status could suggest a different or more benign pattern of tumor progression in elderly patients [7,[19][20][21] .…”
Section: Discussionmentioning
confidence: 99%
“…9 The latest study by Wang et al, based on the National Breast Cancer Audit between 1999 and 2006, found that the proportion of women having reconstruction post mastectomy was highly age dependent, with 27% of women aged 40 or less, 20% of women between 41 and 50 years, 9.4% of women between 51 and 70 years, and less than 1% in women above 70 years having reconstructions. 10 On the contrary, reconstruction rates in the UK have been reported as high as 32% (21% immediate and 11% delayed) 11 and recent U.S. data show immediate reconstruction rates of 38%. 12 Reasons for the relatively low uptake rate of reconstruction in Australia are unclear.…”
mentioning
confidence: 96%